THE DYNAMICS OF SCHADENFREUDE IN STUDENT WHATSAPP GROUPS: A PHENOMENOLOGICAL STUDY - Sianipar, Yules Orlando; Rafli, Zainal; Murtadho, Fathiaty; Anwar, Miftahulkhairah; Prihantoro, Prihantoro (JURNAL EDUSCIENCE, 2025)
Purpose-This study was conducted to show that speech acts in WhatsApp conversations can be a factor in the emergence of Schadenfreude. This study aims to show what kind of speech acts significantly influence the emergence of Schadenfreude and describe the kinds of Schadenfreude that often occur from these speech acts.Methodology-The type of research that was conducted is qualitative research with a phenomenological design. Researchers apply MDAP (Manual Data Analysis Procedure) to analyze data sources to become data. MDAP, or Manual Data Analysis Procedure, is a qualitative research data analysis method that helps researchers analyze their research data.Findings-From the results, a picture of the Schadenfreude phenomenon is formed by perlocutionary speech acts. Any Schadenfreude in perlocutionary speech acts will be able to trigger responses from other students to join in making fun of what is being discussed. The most common types of Schadenfreude are compensation and Aggression. Compensation because they both feel the same difficulty at the same time. Aggression occurs because they are in the same group or want to try to be accepted by others, so they do the same thing: Schadenfreude.Signifinace-It can be seen that Schadenfreude is related to bullying. The factors that cause bullying are internal factors (mental and emotional health, such as high and low empathy, for example, Schadenfreude) and external factors (family, peers, school (one of which is the school climate, and the surrounding area).Keywords: Schadenfreude Speech acts WhatsApp groups Phenomenology MDAP (Manual Data Analysis Procedure)